PENGEMBANGAN SUMBER DAYA WANITA DALAM MENGHADAPI ERA GLOBALISASI* - Prijono Tjiptoherijanto (Populasi, 1996)
In the past, the role of a woman was more of bringing up children and giving company to her husband than anythingelse, but because of the economic changes and education, there are now many house wives who, in the recent days, do not only function as household managers, but they also take on careers outside the home. The perception of the community on women who work outside their families is also becoming more permissive. Generally,women havegot wide opportunities to improve on them selves. Even with this however, there are still internal obstacles which tend to hinder this improvement of women. Various efforts have so far been made to assist women in optimizing themselves according to their individual potentialities. For that matter therefore, Prijono Tjiptoherijanto explains the necessity of improving on the quality of women, either through the family or through other institutional means.